Quantitative μPET Imaging of Cerebral Glucose Metabolism and Amyloidosis in the TASTPM Double Transgenic Mouse Model of Alzheimer’s Disease - Waldron, Ann-Marie; Wyffels, Leonie; Verhaeghe, Jeroen; Bottelbergs, Astrid; Richardson, Jill; Kelley, Jonathan; Schmidt, Mark; Stroobants, Sigrid; Langlois, Xavier; Staelens, Steven (Current Alzheimer Research, 2015)
Positron emission tomography studies of cerebral glucose utilization and amyloid-β deposition with fluoro-deoxy-D-glucose ([18F]-FDG) and amyloid tracers have shown characteristic pathological changes in Alzheimer’s Disease that can be used for disease diagnosis and monitoring. Application of this technology to preclinical research with transgenic animal models would greatly facilitate drug discovery and further understanding of disease processes. The results from preclinical studies with these imaging biomarkers have however been highly inconsistent, causing doubts over whether animal models can truly replicate an AD-like phenotype. In this study we performed in vivo imaging with [18F]-FDG and [18F]-AV45 in double transgenic TASTPM mice, a transgenic model that been previously demonstrated high levels of fibrillar amyloid-β and decreases in cerebral glucose utilization with ex vivo techniques. Our results show widespread and significant retention of [18F]-AV45 (p < 0.0001) in aged TASTPM mice in addition to significantregional decreases in [18F]-FDG uptake (p < 0.05). In vivo quantification of amyloid-β showed a strong (Pearson’s r = 0.7078), but not significant (p = 0.1156), positive correlation with ex vivo measures suggesting some limitations on tracer sensitivity. In the case of [18F]-FDG, voxelwise analysis greatly enhanced detection of hypometabolic regions. We further evidenced modest neuronal loss (thalamus p = 0.0318) that could underlie the observed hypometabolism. This research was performed in conjunction with the European Community's Seventh Framework Program (FP7/2007-2013) for the Innovative Medicine Initiative under the PharmaCog Grant Agreement no.115009.
Keywords: [18F]-AV45